Analysis of the influence of environmental performance and environmental costs on financial performance: The role of corporate social responsibility (CSR) as a moderating variable - Dade Nurdiniah; Iren Meita; Bunga Lestari (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to analyze corporate social responsibility (CSR) in moderating the effect of environmental performance and environmental costs on financial performance in manufacturing companies that are members of the Company Performance Rating Assessment Program (PROPER). This study uses secondary data from the annual financial reports of companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The analysis techniques used include multiple linear regression tests and Moderated Regression Analysis (MRA) tests. Samples were obtained using the purposive sampling method and resulted in 156 observations. The results of the study indicate that environmental performance has an effect on financial performance, while environmental costs have a negative impact on financial performance. CSR as a moderating variable is able to strengthen the effect of environmental performance on financial performance, but cannot strengthen the effect of environmental costs on financial performance.